The Effect of People Business Credit (KUR) on Rice Field Business Income in Tinanggea District - Susriani Susriani; Azhar Bafadal; Yusna Indarsyih (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2022)
Lack of capital in farming can lead to a lack of input, causing a risk of failure or low production. The problem regarding the lack of capital is faced by farmers so that to achieve progress in farming usually takes a very long time. Therefore, farmers in Lanowulu Village and Roraya Village take credit to increase farming capital. This study aims to determine the difference in lowland rice farming income before and after receiving KUR and to determine the effect of KUR on farm income in Tinanggea District, South Konawe Regency. The population in this study were all 60 farmers in Lanowulu Village and Roraya Village who received KUR. Sampling was carried out using a non-probability sampling method, namely through the saturated sampling method (census), where the entire population was sampled. Analysis of the data used is the T-Test test to determine the difference in income before and after receiving KUR and multiple linear regression analysis to determine the effect of KUR on rice farming income after receiving KUR. The results showed that there were differences in the income of lowland rice farming before receiving KUR and after receiving KUR. Farming income after receiving KUR with a significance value of 0.000. People's Business Credit (credit amount, credit usage, credit installment) has a significant effect on farm income in Tinanggea District, South Konawe Regency.